Value of children's luggage using Kansei engineering methodology - Mingrun, Wang (2020)
In the past ten years, due to the increase in the frequency of children’s longdistance travel, children’s luggage companies have begun to design luggage especially for children. Nowadays, many Chinese children have to travel every year. In addition to facilitating children to handle their own belongings and develop their independent skills, having children's luggage can also reduce the burden on parents. However, the probability of children owning their luggage is still low until now. The lack of right value determination of children's luggage has led to parents' low desire to purchase children's luggage. Consumers develop criteria for preference judgement due to their specific values. Consumer experience is considered an important source of competitive advantage, it affects consumer’s purchase intention and satisfaction. Thus, it is important to understand the consumer experiences of children’s luggage to determine the value of children’s luggage. Therefore, to support the sales of children’s luggage and enhance the development of children’s luggage industry, this study targets to determine the value of children’s luggage by using Kansei Engineering methodology based on consumer experience. By evaluating the existing items, the new features of children's luggage were established. The important consumer experiences of children’s luggage were identified through using Experience Map. The value of children’s luggage was determined through using Kansei Engineering methodology. The findings will help product designers to design a children’s luggage with more strategic advantages to support children's luggage sales and improve luggage industry.